Factors associated with anti-retroviral therapy adherence among people living with HIV visiting IRT Perundurai medical college hospital link ART centre, Perundurai, Tamilnadu, India - Vedhanayagam, Mohankumar; Rajagopalan, Rajesh; Rajendran, Balamurgan Bhavani; Sengodan, Sendhil; Sengodan, Senthilkumar (International Journal of Advances in Medicine, 2016)
Background: National AIDS control organisation aims to provide wholesome management to PLHIV. This is ensured by universal access to free and comprehensive care, support and treatment in health delivery facilities across the country by dynamic linkages and referral mechanism for monitoring, mentoring, decentralization and specialized care and treatment. Objective of the study was to analyse factors associated with ART adherence among PLHIV visiting IRT Perundurai Medical College Hospital link ART centre, Tamilnadu, India. Methods: A prospective observational study was conducted during June 2015 to May 2016. All PLHIV receiving ART drugs as per protocol from LAC were included. Results: 139 clients were registered for treatment and follow up till May 2016 in our centre. 31 were transferred to nearby ART, link ART centres. Currently 98 (38 male; 60 female) were utilizing our services. Majority of the patients were on ZLN followed by TLE and ZLE. Most of clients were from rural areas belonging to low or low middle income group. Common occupation was found to be farming and cattle rearing. Most women were housewives. The average age in present study was 38.3 years. Oldest was 73 years old male and youngest 10 years old female. Family support and benefits of ART drugs tops the list of facilitators; supply chain, alcohol issues, family issues were commonly observed barriers. Conclusions: Our results supported the measurement of multiple dimensions of medication-taking behaviours in order to avoid overestimating adherence to ART. Investigation of factors associated with long term adherence would require elaborate and constant follow-ups than in this study period.